ISLAMIC ETHICS TOWARDS SOCIAL RESILIENCE: BUILDING AN INCLUSIVE AND SUSTAINABLE SOCIETY - Firza Agung Prakoso; Abd. Adim; Yuni Astriana Khamidah; Nunuk Khomariyah; Aprilia Cintya Dewi (International Conference on Humanity Education and Society (ICHES), 2026)
This study aims to explore the transformation of Islamic ethics (Akhlaq) from the individual realm to a strategic framework in building inclusive and sustainable social resilience. Amidst global challenges such as social polarization, economic inequality, and ecological crises, Islamic values offer a solution paradigm through the principle of Rahmatan lil 'Alamin . Using descriptive research methods and the Maqasid al-Shari'ah approach , this study analyzes how the concepts of justice ('Adl), moderation (Wasathiyah), and ecological responsibility (Khalifah) are implemented in the structure of modern society. The results show that Islamic ethics functions as social capital that strengthens intergroup cohesion through the recognition of human dignity without discrimination. This study concludes that strengthening inclusive social resilience requires an integration between spiritual values and public policies based on the public good. The implementation of environmental ethics (Fiqh al-Bi'ah) is also key in guaranteeing the rights of future generations to natural resources.